Bioactive Spirobisnaphthalenes and Lactones from a Cup Fungus Plectania sp. Collected in the Tibet Plateau Region. Issue 25 (11th August 2016) - Wang, Kai; Bao, Li; Ma, Ke; Qi, Wei; Song, Fuhang; Yao, Yijian; Yin, Wenbing; Zhang, Lixin; Huang, Ying; Han, Junjie; Liu, Hongwei
Abstract : Five new spirobisnaphthalenes (1 –5 ), one new tetralone derivative (6 ), and six new lactones (7 –12 ) together with the known compound urnucratin C (13 ) have been isolated from the solid culture of the cup fungus Plectania sp. The structures of the new compounds were unambiguously elucidated on the basis of one‐ and two‐dimensional NMR spectroscopy, high‐resolution mass spectrometry, and circular dichroism (CD) spectroscopy. Compounds1 –6 were found to be active against Staphylococcus aureus, methicillin‐resistant S. aureus (MRSA), Bacillus subtilis, and Pseudomonas aeruginosa . In addition, the cytotoxicities of1 –13 were evaluated against the HepG2 and K562 cell lines by using the CCK8 assay. Compounds1 –3 and13 showed moderate cytotoxicity against HepG2 and K562 with IC50 values in the range 10.7–38.5 µm . This is the first report of secondary metabolites from this cup fungus. Abstract : Twelve new natural products (1 –12 ) and the known urnucratin C (13 ) have been isolated from the solid culture of the cup fungus Plectania sp. and their structures unambiguously elucidated by spectroscopic methods. Compounds1 –6 were found to show antibacterial activity and compounds1 –3 and13 showed moderate cytotoxicity against the HepG2 and K562 cell lines.